Effect of Ni precursor salts on Ni-mayenite catalysts for steam methane reforming and on Ni-CaO-mayenite materials for sorption enhanced steam methane reforming. (8th March 2019) - Di Giuliano, A.; Gallucci, K.; Foscolo, P.U.; Courson, C.
Abstract: In view of climate change containment, sorption enhanced steam methane reforming (SESMR) appears as an interesting production route for H2 with the additional advantage of CO2 capture application performed by high-temperature solid sorbents. CaO is largely employed as CO2 sorbent because of its low-cost mineralized forms (limestone and dolomite), of its high sorption capacity in the high temperature range compatible with steam methane reforming (SMR). Many recent studies have proposed purposely synthesized Ni-based reforming catalysts, used with high-temperature CO2 solid sorbents, or combined sorbent-catalyst materials (CSCM). For this last purpose, we studied the effect of Ni salt precursor (Ni nitrate hexahydrate or Ni acetate tetrahydrate) on properties and reactivity of Ni-mayenite catalysts or Ni-CaO-mayenite CSCM, synthesized by an already validated sequence of wet mixing (for sorbents synthesis) and wet impregnation (for catalysts and CSCM synthesis) methods. Although Ni acetate tetrahydrate was often reported as the best choice to improve textural properties, our study identified Ni nitrate hexahydrate as a definitely more suitable precursor than Ni acetate tetrahydrate in the purpose of developing efficient materials for SESMR. The dissimilar behaviors observed in reforming reactivity are related and explained by the differences in textural properties, Ni species dispersion, and reducibility. Graphical abstract: Image 1 Highlights: Study of Steam Methane Reforming (SMR)/Sorption Enhanced SMR (SESMR). Ni nitrate hexahydrate Ni(N) or Ni acetate tetrahydrate Ni(Ac) as Ni precursors. Ni precursor salt and its fraction affect textural and reducibility properties. Higher integration with the support of Ni derived from Ni(N) than that from Ni(Ac). SESMR by Ni-CaO-mayenite: materials from Ni(N) more active than those from Ni(Ac).